Diel variation in the vertical distribution of deep-water scattering layers in the Gulf of Mexico. (September 2016) - D'Elia, Marta; Warren, Joseph D.; Rodriguez-Pinto, Ivan; Sutton, Tracey T.; Cook, April; Boswell, Kevin M.
Abstract: Sound scattering layers (SSLs) are important components of oceanic ecosystems with ubiquitous distribution throughout the world's oceans. This vertical movement is an important mechanism for exchanging organic matter from the surface to the deep ocean, as many of the organisms comprising SSLs serve as prey resources for linking the lower trophic levels to larger predators. Variations in abundance and taxonomic composition of mesopelagic organisms were quantified using repeated discrete net sampling and acoustics over a 30-h survey, performed during 26–27 June 2011 at single site (27°28'51"N and 88°27'54"W) in the northern Gulf of Mexico. We acoustically classified the mesopelagic SSL into four broad taxonomic categories, crustacean and small non-swimbladdered fish (CSNSBF), large non-swimbladdered fish (LNSBF), swimbladdered fish (SBF) and unclassified and we quantified the abundance of mesopelagic organisms over three discrete depth intervals; epipelagic (0–200 m); upper mesopelagic (200–600 m) and lower mesopelagic (600–1000 m). Irrespective of the acoustic categories at dusk part of the acoustic energy redistributed from the mesopelagic into the upper epipelagic (shallower than 100 m) remaining however below the thermocline depth. At night higher variability in species composition was observed between 100 and 200 m suggested that a redistribution of organisms may also occur within the upper portion of the water column. Along the upper mesopelagic backscatter spectra from CSNSBF migrated between 400 and 460 m while spectra from the other categories moved to shallower depths (300 and 350 m), resulting in habitat separation from CSNSBF. Relatively small vertical changes in both acoustic backscatter and center of mass metrics of the deep mesopelagic were observed for CNSBF and LNSBF suggesting that these animals may be tightly connected to deeper (below 1000 m) mesopelagic habitats, and do not routinely migrate into the epipelagic. Highlights: Backscattering spectra were used to classify layers in the Gulf of Mexico. Scattering layers were categorized into four taxonomic groups. The center of mass for all categories remained below the thermocline. Differential use of vertical habitat by specific taxonomic groups was observed.